FORMAL STRUCTURE OF TERMINOLOGY LEXEMAS IN INTERNATIONAL TOURISM - Urinova Sitorabonu Baxtiyerovna (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the problems of translation of international tourism, the analysis of the formal structure of the researched terminology lexemes, as well as the information about the structure of monolexemic units in the terminology of international tourism are widely covered.